Perivascular adipose tissue dysfunction aggravates adventitial remodeling in obese mini pigs via NLRP3 inflammasome/IL-1 signaling pathway - Zhu, Xiao; Zhang, Hong-wen; Chen, Hai-nan; Deng, Xiao-jun; Tu, Yi-xuan; Jackson, Ampadu O.; Qing, Ji-na; Wang, Ai-ping; Patel, Vaibhav; Yin, Kai (Acta pharmacologica Sinica, 2019)
Perivascular adipose tissue (PVAT), a special type of adipose tissue, closely surrounds vascular adventitia and produces numerous bioactive substances to maintain vascular homeostasis. PVAT dysfunction has a crucial role in regulating vascular remodeling, but the exact mechanisms remain unclear. In this study, we investigated whether and how obesity-induced PVAT dysfunction affected adventitia remodeling in early vascular injury stages. Mini pigs were fed a high sugar and fat diet for 6 months to induce metabolic syndrome and obesity. In the mini pigs, left carotid vascular injury was then generated using balloon dilation. Compared with normal mini pigs, obese mini pigs displayed significantly enhanced vascular injury-induced adventitial responses, evidenced by adventitia fibroblast (AF) proliferation and differentiation, and adventitia fibrosis, as well as exacerbated PVAT dysfunction characterized by increased accumulation of resident macrophages, particularly the M1 pro-inflammatory phenotype, increased expression of leptin and decreased expression of adiponectin, and production of pro-inflammatory cytokines interleukin (IL)-1β and IL-18. Primary AFs cultured in PVAT-conditioned medium from obese mini pigs also showed significantly increased proliferation and differentiation. We further revealed that activated nod-like receptor protein 3 (NLRP3) inflammasome and its downstream products, i.e., IL-1 family members such as IL-1β and IL-18 were upregulated in the PVAT of obese mini pigs; PVAT dysfunction was also demonstrated in preadipocytes treated with palmitic acid. Finally, we showed that pretreatment with IL-1 receptor (IL-1R) antagonist or IL-1R knockdown blocked AF proliferation and differentiation in AFs cultured in PVAT-conditioned medium. These results demonstrate that obesity-induced PVAT dysfunction aggravates adventitial remodeling after early vascular injury with elevated AF proliferation and differentiation via activating the NLRP3/IL-1 signaling pathway.